Comparative pharmacokinetics of maxacalcitol in healthy Taiwanese and Japanese subjects. Issue 3 (March 2020) - Liu, Ming-Che; Chou, Feng-Yi; Chien, Yi-An; Chen, Yen-Ju; Abe, Masaichi; Furusho, Koki; Matsuki, Shunji
Abstract: Pharmacokinetic studies of maxacalcitol in healthy Taiwanese subjects have been conducted. This study to compare the pharmacokinetic properties of maxacalcitol in healthy Taiwanese and Japanese subjects. Healthy male Taiwanese subjects (n = 24) and healthy male Japanese subjects (n = 24) were enrolled in separate single-center and received a single intravenous dose of 1.25, 2.5 and 5 μg maxacalcitol. Male subjects were exclusively employed in the study due to the first administration of maxacalcitol to Taiwanese. Serum samples were collected for up to 72 h for pharmacokinetic analysis, and safety was assessed. Exposures to maxacalcitol as mean C5 and AUCinf appeared to increase with increase of doses in Taiwanese subjects (C5 : 74.0, 159, and 321 pg/mL; AUCinf : 473, 763, and 1460 h･pg/mL) and Japanese subjects (C5 : 92.9, 174, and 346 pg/mL; AUCinf : 312, 588, and 1040 h･pg/mL). After single bolus IV administration, linearity in maxacalcitol exposure was shown over the dose range of 1.25–5 μg in both Taiwanese and Japanese male healthy subjects. C5 of maxacalcitol was slightly lower (85%) in Taiwanese compared with that in Japanese and AUCinf of maxacalcitol in Taiwanese subjects was contrarily 15.0 (41.6%) higher than that in Japanese subjects, resulted in not much difference in pharmacokinetics of maxacalcitol between Taiwanese and Japanese. Moreover, maxacalcitol was well tolerated in both healthy Taiwanese and Japanese subjects. Abstract : Maxacalcitol, Pharamcokinetics, Phase I study, Oxarol, Direct comparison study, Physical chemistry; Pharmaceutical science; Musculoskeletal system; Renal system; Pharmacology.